Small‐signal stability‐constrained optimal power flow analysis of multiterminal VSC‐HVDC systems with large‐scale wind farms. Issue 7 (22nd March 2019) - Kim, Sangwon; Yokoyama, Akihiko; Takaguchi, Yusuke; Takano, Tomihiro; Mori, Kazuyuki; Izui, Yoshio
Abstract : As a solution for the large‐scale wind power transmission in a power system model in East Japan, multiterminal VSC‐HVDC systems are proposed to be installed in the system model. To evaluate the effectiveness of the systems, small‐signal stability‐constrained optimal power flow (SSSC‐OPF) analysis in mixed AC/multiterminal VSC‐HVDC systems is developed. It is revealed by SSSC‐OPF analysis that the system reinforced only by an AC system is exposed to unstable operations. In contrast, mixed AC/multiterminal VSC‐HVDC systems do not suffer from such unstable system operations. On top of that, the differences in multiterminal VSC‐HVDC systems with different configurations are also discussed. Different annual fuel costs and wind power hosting capacity results are obtained due to AC transmission line capacities and interarea oscillation modes. The best multiterminal VSC‐HVDC system among all simulated multiterminal VSC‐HVDC systems is also concluded. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.